Conducting the Needs Assessment #4: Audience Motivations, Barriers, and Objections - Laura A. Sanagorski Warner; Matt Benge (EDIS)
A successful needs assessment is contingent on participation from the right people, so understanding potential motivations, barriers, and objections specific to your participants is critical. This new 5-page publication, the fourth in the Conducting the Needs Assessment series, provides Extension educators and other service providers with an overview of motivations, barriers, and objections specific to participants in needs assessments. Written by Laura Warner and Matt Benge and published by the UF/IFAS Department of Agricultural Education and Communication. https://edis.ifas.ufl.edu/wc342